Laminated cell and lithium ion secondary battery

By setting a resistive layer on the surface of the positive active layer of the single-sided positive electrode sheet to increase the resistivity, the problem of easy lithium precipitation in the negative electrode in the stacked battery is solved, and the safety performance and cycle performance of the battery are improved.

CN119340454APending Publication Date: 2025-01-21ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411600575.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the existing stacked-type batteries, the negative electrode corresponding to the single-sided positive electrode plate is prone to lithium removal, resulting in the battery safety performance and cycling performance being affected.

Method used

A resistance layer is provided on the surface of the positive active layer of the single-sided positive electrode sheet so that the resistivity of the single-sided positive electrode sheet reaches 0.3kΩ·cm-2kΩ·cm. The high-impedance resistive layer can reduce the delithium speed of the single-sided positive electrode sheet during charging. Improve the lithium deposition problem of the negative electrode corresponding to the single-sided positive electrode sheet.

Benefits of technology

By increasing the resistivity of the single-sided positive electrode sheet and reducing the lithium removal rate during charging, the lithium deposition problem of the negative electrode corresponding to the single-sided positive electrode sheet is significantly improved, and the safety performance and cycle performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340454A_ABST
    Figure CN119340454A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion batteries, and discloses a laminated cell and a lithium ion secondary battery. The laminated battery cell comprises a plurality of positive plates and a plurality of negative plates which are alternately laminated, a diaphragm is arranged between the adjacent positive plate and negative plate, and the outermost layer of pole plate of the laminated battery cell is a single-sided positive plate; the single-sided positive plate comprises an outermost current collector, a positive active layer and a resistive layer which are laminated towards the inner direction of the laminated cell, the resistive layer at least covers the surface, far away from the outermost current collector, of the positive active layer, and the resistive layer faces the diaphragm; and the resistivity of the single-sided positive plate is 0.3 k omega.cm to 2 k omega.cm. By arranging the high-impedance resistance layer on the surface of the positive active layer of the single-sided positive plate, the lithium removal speed of the single-sided positive plate during charging can be reduced, and the lithium precipitation problem of a negative electrode corresponding to the single-sided positive plate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a laminated battery cell and a lithium-ion secondary battery. Background Art

[0002] The battery manufacturing process is mainly divided into two technical routes: stacking process and winding process. Compared with winding batteries, secondary batteries with stacking structure show great advantages in energy density, safety, cycle life, etc., prompting a large number of battery companies to enter the stacking field.

[0003] In order to improve the energy density, the outermost electrode of the laminated battery is usually designed as a single-sided positive electrode, that is, the positive electrode active material layer is only set on one side of the outermost current collector, which leads to uneven stress on both sides of the current collector, which is easy to curl, and the single-sided electrode is easy to warp during the cycle, affecting the safety and cycle performance of the battery. To solve the above problems, the usual practice is to increase the thickness of the outermost current collector to overcome the stress, but this will bring new problems: the current density on the outermost current collector is large, which makes the negative electrode corresponding to the single-sided positive electrode easy to deposit lithium. Summary of the invention

[0004] In view of this, the present application provides a laminated battery cell and a lithium-ion secondary battery, which aims to solve the problem of easy lithium deposition in the negative electrode corresponding to the single-sided positive electrode sheet in the existing laminated battery to a certain extent.

[0005] According to an embodiment of the present application, in a first aspect, the laminated battery core provided by the present application comprises a plurality of positive electrode sheets and a plurality of negative electrode sheets alternately stacked, a separator is arranged between adjacent positive electrode sheets and negative electrode sheets, and the outermost electrode sheet of the laminated battery core is a single-sided positive electrode sheet;

[0006] The single-sided positive electrode sheet includes an outermost current collector, a positive active layer and a resistance layer stacked toward the inner direction of the laminated battery core, the resistance layer at least covers the surface of the positive active layer away from the outermost current collector, and the resistance layer faces the diaphragm; the resistivity R0 of the single-sided positive electrode sheet is 0.3kΩ·cm-2kΩ·cm.

[0007] In an optional embodiment, the unit area mm of the resistor layer 2 A difference D between a maximum value of the thickness of the resistor layer and a minimum value of the thickness of the resistor layer satisfies: D ≥ 0.5 μm.

[0008] In an optional embodiment, the adhesion force N1 between the resistor layer and the positive electrode active layer and the adhesion force N2 between the outermost current collector and the positive electrode active layer satisfy: N1>N2.

[0009] In an optional implementation, the thickness H1 of the resistance layer and the thickness H2 of the positive electrode active layer satisfy: H2 / H1≥5.

[0010] In an optional embodiment, the resistance layer includes 80%-95% of inorganic particles and 5%-20% of a binder.

[0011] In an optional embodiment, the median particle size Dv501 of the inorganic particles and the median particle size Dv502 of the active particles in the positive electrode active layer satisfy: Dv502 / Dv501≥10.

[0012] In an optional embodiment, the inorganic particles include at least one of silicon dioxide, aluminum oxide, calcium oxide, titanium oxide, boehmite, magnesium oxide, and magnesium hydroxide.

[0013] In an optional embodiment, the Dv501 is 0.01 μm-1 μm.

[0014] In an optional embodiment, the Dv501 is 0.01 μm-0.1 μm.

[0015] In an optional embodiment, the Dv502 is 10 μm-20 μm.

[0016] In an optional embodiment, the N1 is 1.5 gf / mm-9 gf / mm.

[0017] In an optional embodiment, the N2 is 0.3 gf / mm-1 gf / mm.

[0018] In an optional embodiment, the H1 is 0.5 μm-6 μm.

[0019] In an optional embodiment, the H2 is 30 μm-80 μm.

[0020] In an optional embodiment, the inner positive electrode sheet disposed between the two outermost electrode sheets in the laminated battery core comprises a double-sided positive electrode sheet;

[0021] The surface resistance R1 of the single-sided positive electrode sheet and the surface resistance R2 of the double-sided positive electrode sheet satisfy: R1>1 / 2R2.

[0022] In an optional embodiment, the porosity P1 of the single-sided positive electrode sheet and the porosity P2 of the double-sided positive electrode sheet satisfy: P2>P1.

[0023] In an optional embodiment, the R1 is 0.3Ω / cm-2Ω / cm.

[0024] In an optional embodiment, the R2 is 0.2Ω / cm-2Ω / cm.

[0025] In an optional embodiment, the P1 is 15%-30%.

[0026] In an optional embodiment, the P2 is 20%-40%.

[0027] In an optional embodiment, the thickness of the outermost current collector is 12 μm-25 μm.

[0028] In an optional embodiment, the thickness of the current collector of the double-sided positive electrode sheet is 6 μm-10 μm.

[0029] In an optional embodiment, the diaphragm disposed toward the resistance layer is a thermal composite diaphragm, and the adhesion force N3 between the thermal composite diaphragm and the resistance layer is 0.1 gf / mm-2 gf / mm.

[0030] In an optional embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer arranged on the surface of the negative electrode current collector, the negative electrode active layer includes a negative electrode active material, and the negative electrode active material includes a silicon material; the resistivity R3 of the negative electrode sheet satisfies: 60Ω·cm≥R3≥2Ω·cm.

[0031] According to an embodiment of the present application, in a second aspect, a lithium-ion secondary battery is provided, comprising the laminated battery cell described in the first aspect of the present application.

[0032] In an optional embodiment, the lithium-ion secondary battery further includes an electrolyte, the content of the carboxylate solvent in the electrolyte is A% and 50≥A≥10, the content of the adhesive in the resistance layer is B% and 20≥B≥5, and A and B satisfy: 10≥A / B≥0.5.

[0033] The technical solution of this application has the following advantages:

[0034] The lithium-ion secondary battery provided by the present application is provided with a resistance layer on the surface of the positive electrode active layer of the single-sided positive electrode sheet so that the resistivity of the single-sided positive electrode sheet reaches 0.3kΩ·cm-2kΩ·cm. The high-impedance resistance layer can reduce the lithium desorption rate of the single-sided positive electrode sheet during charging, thereby improving the lithium plating problem of the negative electrode corresponding to the single-sided positive electrode sheet.

[0035] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0037] Figure 1 It is a schematic diagram of the structure of a laminated battery cell in one embodiment of the present application.

[0038] Figure 2 This is a SEM image of the cross section of the outermost positive electrode sheet prepared in Example A of the present application.

[0039] The reference numerals are described as follows:

[0040] 1. Inner positive electrode sheet; 2. Negative electrode sheet; 3. Outer positive electrode sheet; 101. Inner positive electrode active layer; 102. Inner positive electrode current collector; 103. Negative electrode active layer; 104. Negative electrode current collector; 105. Resistance layer; 106. Positive electrode active layer; 107. Outer current collector. DETAILED DESCRIPTION

[0041] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0042] It should be noted that the terms "inside" and "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present application. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0043] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0044] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.

[0045] In order to solve the problem that the negative electrode corresponding to the single-sided positive electrode sheet in the existing stacked battery is prone to lithium deposition, the present application provides the following solution.

[0046] According to a first aspect of the present application, a laminated battery core is provided, comprising a plurality of positive electrode sheets and a plurality of negative electrode sheets alternately stacked, a separator is provided between adjacent positive electrode sheets and negative electrode sheets, and the outermost electrode sheet of the laminated battery core is a single-sided positive electrode sheet;

[0047] The single-sided positive electrode sheet includes an outermost current collector, a positive active layer and a resistance layer stacked toward the inner direction of the laminated battery core, the resistance layer at least covers the surface of the positive active layer away from the outermost current collector, and the resistance layer faces the diaphragm; the resistivity R0 of the single-sided positive electrode sheet is 0.3kΩ·cm-2kΩ·cm.

[0048] It should be noted that the conventional single-sided positive electrode sheet (i.e., the outermost positive electrode sheet that only includes the current collector and the positive electrode active layer on one side of the surface) has a relatively thick outermost current collector, usually 12μm-25μm, so the resistivity is relatively low, generally less than 0.3kΩ·cm, resulting in a higher current density on the single-sided positive electrode sheet, which accelerates the deintercalation speed of lithium ions. The present application sets a resistance layer on the surface of the positive electrode active layer of the single-sided positive electrode sheet, so that the resistivity of the single-sided positive electrode sheet reaches 0.3kΩ·cm-2kΩ·cm. The high-impedance resistance layer can reduce the lithium deintercalation speed of the single-sided positive electrode sheet during charging, and improve the lithium precipitation problem of the negative electrode corresponding to the single-sided positive electrode sheet. As an example, the resistivity R0 of a single-sided positive electrode sheet may be 0.3 kΩ·cm, 0.6 kΩ·cm, 0.8 kΩ·cm, 1 kΩ·cm, 1.2 kΩ·cm, 1.4 kΩ·cm, 1.6 kΩ·cm, 1.8 kΩ·cm, 2 kΩ·cm, etc., or may be within the range of any two of the above values.

[0049] It can be understood that the laminated battery cell in the present application is stacked in the order of first electrode sheet-diaphragm-second electrode sheet-diaphragm-first electrode sheet-diaphragm...diaphragm-second electrode sheet-diaphragm-first electrode sheet. Therefore, the first electrode sheet stacked first and the last electrode sheet stacked are both the outermost electrode sheets, and the first electrode sheet between the first electrode sheet stacked first and the last electrode sheet stacked is the inner electrode sheet. Figure 1 As an example, the structure of a laminated battery cell in one embodiment of the present application is further described. Figure 1As shown, in the height direction of the laminated battery cell, the outermost positive electrode sheet 3, the separator (not shown in the figure), the negative electrode sheet 2, the separator, ... the negative electrode sheet 2, the separator, the inner positive electrode sheet 1, the separator, the negative electrode sheet 2, the separator ... the negative electrode sheet 2, the separator and the outermost positive electrode sheet 3 are stacked in sequence from top to bottom; wherein, the inner positive electrode sheet 1 includes an inner positive electrode collector 102 and an inner positive electrode active layer 101 arranged on two side surfaces in the thickness direction of the inner positive electrode collector 102, the negative electrode sheet 2 includes a negative electrode collector 104 and a negative electrode active layer 103 arranged on two side surfaces in the thickness direction of the negative electrode collector 104, and the outermost positive electrode sheet 3 includes an outermost current collector 107, a positive electrode active layer 106 and a resistor layer 105 which are stacked.

[0050] Furthermore, the positive electrode active layer includes positive electrode active materials. The particle size of the positive electrode active materials and the thickness of the positive electrode active layer jointly determine that the surface of the positive electrode active layer is not a plane, which makes the thickness of the resistance layer covering the surface of the positive electrode active layer vary. For example, the thickness of the resistance layer in the first region is 2.41 μm, the thickness of the resistance layer in the second region is 1.43 μm, the thickness of the resistance layer in the third region is 1.97 μm, and the thickness of the resistance layer in the fourth region is 0.793 μm. It can be concluded that the unit area mm of the resistance layer 2 The difference D between the maximum value of the thickness of the resistor layer and the minimum value of the thickness of the resistor layer satisfies: D ≥ 0.5 μm. This indicates that the resistor layer is partially embedded in the positive electrode active layer, which can improve the bonding effect between the resistor layer and the positive electrode active layer on the one hand, and avoid the excessive thickness of the battery cell due to the addition of the resistor layer, thereby losing energy density.

[0051] Furthermore, the adhesion between the resistance layer and the positive electrode active layer is defined as N1, the adhesion between the outermost current collector and the positive electrode active layer is defined as N2, and N1 and N2 satisfy: N1>N2. In this way, on the basis of increasing the impedance of the single-sided positive electrode sheet to reduce the lithium desorption rate of the single-sided positive electrode sheet during charging, thereby improving the lithium deposition of the negative electrode corresponding to the single-sided positive electrode sheet, the interface impedance between the resistance layer and the positive electrode active layer can be further reduced, thereby improving the electrical performance of the battery cell. In some embodiments, N1 is 1.5gf / mm-9gf / mm. As an example, N1 can be 1.5gf / mm, 3gf / mm, 4.5gf / mm, 6gf / mm, 7.5gf / mm, 9gf / mm, etc., or is within the range of any two of the above values; N2 is 0.3gf / mm-1gf / mm. As an example, N2 can be 0.3gf / mm, 0.4gf / mm, 0.5gf / mm, 0.6gf / mm, 0.7gf / mm, 0.8gf / mm, 0.9gf / mm, 1gf / mm, etc., or is within the range of any two of the above values.

[0052] In order to minimize the battery energy density loss, it is necessary to ensure that the thickness of the resistance layer is as small as possible. Therefore, in the present application, the thickness H1 of the resistance layer and the thickness H2 of the positive electrode active layer satisfy: H2 / H1≥5. This ensures the high impedance of the single-sided positive electrode sheet to reduce the lithium desorption rate of the single-sided positive electrode sheet during charging, thereby improving the lithium plating of the negative electrode corresponding to the single-sided positive electrode sheet, thereby further reducing the energy density loss of the battery. In some embodiments, H1 is 0.5μm-6μm. As an example, H1 can be 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, etc., or is within the range of any two of the above values; H2 is 30μm-80μm. As an example, H2 can be 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, etc., or is within the range of any two of the above values.

[0053] Specifically, the resistor layer described in the present application includes 80%-95% of inorganic particles and 5%-20% of adhesive. It should be noted that the content of adhesive in the inner positive electrode sheet between the two outermost electrodes of the laminated battery core is usually about 1%. By increasing the content of adhesive in the resistor layer, the present application can not only ensure the bonding effect between the resistor layer and the positive active layer and the diaphragm, but more importantly, after the resistor layer swells in contact with the electrolyte, the high content of adhesive can provide more impedance, which helps to improve the resistivity of the single-sided positive electrode sheet. According to the aforementioned function of the resistor layer, the resistor layer of the present application does not contain a conductive agent, and the inorganic particles are not conductive. In fact, the inorganic particles in the present application should be high-resistance materials. In some embodiments, the material of the inorganic particles can be, for example, at least one of silicon dioxide, aluminum oxide, calcium oxide, titanium oxide (molecular formula Ti2O3), boehmite, magnesium oxide, and magnesium hydroxide.

[0054] Furthermore, the particle size Dv501 of the inorganic particles and the particle size Dv502 of the active particles in the positive electrode active layer satisfy: Dv502 / Dv501≥10. Small-sized inorganic particles can be embedded between large-sized positive electrode active particles, thereby not only improving the bonding effect between the resistance layer and the positive electrode active layer, but also effectively improving the resistivity of the single-sided positive electrode sheet, so as to achieve the effect of reducing the lithium desorption rate of the single-sided positive electrode sheet during charging and improving the lithium deposition of the negative electrode corresponding to the single-sided positive electrode sheet, but also avoiding excessive increase in the thickness of the battery cell, thereby losing the energy density of the battery. In some embodiments, Dv501 is 0.01μm-1μm. As an example, Dv501 can be 0.01μm, 0.03μm, 0.05μm, 0.07μm, 0.09μm, 0.1μm, 0.3μm, 0.7μm, 1μm, etc., or is within the range of any two of the above values; Dv502 is 10μm-20μm. As an example, Dv502 can be 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, etc., or is within the range of any two of the above values.

[0055] In order to improve battery performance and enhance battery safety, in the laminated battery cell, except for the outermost electrode sheet which is a single-sided positive electrode sheet, the remaining inner electrode sheets (i.e., the electrode sheets arranged between the two outermost electrode sheets) are all double-sided electrode sheets. As the name implies, both surfaces of the inner current collector (thickness is generally 6μm-10μm) are coated with positive electrode active materials to form double-sided positive electrode sheets, or are coated with negative electrode active materials to form double-sided negative electrode sheets. The surface resistance R1 of the single-sided positive electrode sheet described in this application and the surface resistance R2 of the double-sided positive electrode sheet satisfy: R1>1 / 2R2, indicating that the surface impedance of the single-sided positive electrode sheet increases, which can reduce the lithium delithiation rate of the single-sided positive electrode sheet during charging and avoid lithium precipitation of the corresponding negative electrode sheet. In some embodiments, R1 is 0.3Ω / cm-2Ω / cm. As an example, R1 can be 0.3Ω / cm, 0.7Ω / cm, 1.0Ω / cm, 1.3Ω / cm, 1.7Ω / cm, 2.0Ω / cm, etc., or is within the range of any two of the above values; R2 is 0.2Ω / cm-2Ω / cm. As an example, R2 can be 0.2Ω / cm, 0.5Ω / cm, 1.0Ω / cm, 1.5Ω / cm, 2.0Ω / cm, etc., or is within the range of any two of the above values.

[0056] Furthermore, the porosity P1 of the single-sided positive electrode sheet and the porosity P2 of the double-sided positive electrode sheet satisfy: P2>P1. The reduction in the porosity of the single-sided positive electrode sheet, on the one hand, is conducive to increasing the bonding effect between the resistance layer and the positive electrode active layer, which can not only reduce the interface impedance between the two, but also improve the resistivity of the single-sided positive electrode sheet, thereby solving the problem of negative electrode lithium plating corresponding to the single-sided positive electrode sheet, and on the other hand, it can also avoid excessive thickness of the battery cell, thereby helping to reduce the energy density loss of the battery. In some embodiments, P1 is 15%-30%. As an example, P1 can be, for example, 15%, 18%, 20%, 23%, 26%, 30%, etc. or within the range of any two of the above values; P2 is 20%-40%. As an example, P2 can be, for example, 20%, 25%, 30%, 35%, 40%, etc. or within the range of any two of the above values.

[0057] It should be noted that the specific material type of the positive electrode active material is not particularly limited in the present application. As long as it is a positive electrode active material for a lithium-ion secondary battery, it can be applicable to the present application. For example, it can be at least one of lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese iron phosphate, and lithium-rich manganese-based materials.

[0058] Conventional polyethylene or polypropylene diaphragms can be used in the lithium-ion secondary battery of the present application. During the lamination process, the diaphragm and the electrode are preheated and pressed before lamination. The diaphragm treated by this step is called a thermal composite diaphragm. In particular, when the diaphragm arranged toward the resistance layer of the single-sided positive electrode is a thermal composite diaphragm, the bonding effect between the resistance layer and the diaphragm glue layer can be further enhanced to reduce the interface impedance. In some embodiments, the bonding force N3 between the thermal composite diaphragm and the resistance layer is 0.1gf / mm-2gf / mm. As an example, N3 can be 0.1gf / mm, 0.3gf / mm, 0.5gf / mm, 0.7gf / mm, 1gf / mm, 1.2gf / mm, 1.5gf / mm, 1.8gf / mm, 2gf / mm, etc. or within the range of any two of the above values.

[0059] According to a second aspect of the present application, a lithium-ion secondary battery is provided, comprising the laminated battery cell described in the first aspect of the present application.

[0060] The electrolyte is filled between the positive and negative electrodes of lithium-ion secondary batteries. The main components of the electrolyte include organic solvents and electrolyte lithium salts. These components form an environment inside the battery that can conduct ions, allowing lithium ions to move freely between the positive and negative electrodes, thereby realizing the battery's charging and discharging process. In order to improve the dynamic performance of the battery cell, carboxylic acid ester solvents are often used, but this type of solvent will affect the bonding effect of the single-sided positive electrode sheet and is also prone to deteriorating the furnace temperature. Therefore, it is necessary to control the content A% of the carboxylic acid ester solvent in the electrolyte to meet the following conditions: 50≥A≥10 and 10≥A / B≥0.5, where B is the content of the adhesive in the resistor layer. According to the aforementioned value of B, it is 5-20. The high adhesive content can not only ensure the bonding effect between the resistor layer and the positive electrode active layer and the diaphragm, but more importantly, it can provide more impedance after the resistor layer swells in contact with the electrolyte to increase the resistivity of the single-sided positive electrode sheet, thereby solving the problem of negative electrode lithium plating corresponding to the single-sided positive electrode sheet; at the same time, the content of the carboxylic acid ester solvent in the electrolyte also needs to be controlled within an appropriate range, thereby further ensuring the bonding effect between the single-sided positive electrode sheet and the adjacent diaphragm on the basis of ensuring the dynamic balance of the battery cell, thereby helping to improve the safety performance of the battery cell. In some embodiments, the content A% of the carboxylic acid ester solvent in the electrolyte can be, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc. or within the range formed by any two of the above values, and the content B% of the adhesive in the resistor layer can be 5%, 7.5%, 10%, 12.5%, 15%, 17.5%, 20%, etc. or within the range formed by any two of the above values, then the value of A / B can be 0.5, 1, 2, 4, 6, 8, 9, 10, etc. or within the range formed by any two of the above values.

[0061] As an example, the carboxylate solvent in the present application can be methyl formate (MF), ethyl acetate (EA), ethyl propionate (EP), methyl acetate (MA), methyl butyrate (MB), methylpropyl carbonate (MP), propyl propionate (PP), ethyl butyrate (EB) or at least one of their fluorinated products, wherein the fluorinated carboxylic acid ester can be, for example, methyl fluoroformate, ethyl difluoroacetate, ethyl 2-fluoropropionate, methyl fluoroacetate, methyl 4-fluorobutyrate, propyl 2-fluoropropionate, and ethyl 4-fluorobutyrate.

[0062] It is understandable that the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer arranged on the surface of the negative electrode current collector, and the negative electrode active layer includes a negative electrode active material. In some embodiments of the present application, the negative electrode active material can be selected from silicon materials, so that the resistivity R3 of the negative electrode sheet satisfies: 60Ω·cm≥R3≥2Ω·cm. As an example, R3 can be 2Ω·cm, 6Ω·cm, 10Ω·cm, 20Ω·cm, 30Ω·cm, 40Ω·cm, 50Ω·cm, 60Ω·cm, etc. or within the range composed of any two of the above values. This is because the silicon negative electrode has the advantages of high energy density, good safety performance, excellent fast charging performance and low cost. It is used in the lithium-ion secondary battery of the present application, which can significantly improve the energy density of the battery cell, and the resistance layer of the single-sided positive electrode sheet has elastic characteristics in addition to high impedance, which can alleviate the thickness expansion of the silicon negative electrode.

[0063] As an example, the silicon material in the present application can be at least one of elemental silicon, silicon alloy, silicon carbon, and silicon oxygen, and the doping amount of the silicon material can be, for example, 5%, 6%, 7%, 8%, 9%, 10% or within the range of any two of the above values.

[0064] The present application is described in further detail below in conjunction with specific examples, and these examples should not be construed as limiting the scope of protection claimed in the present application. Where specific experimental steps or conditions are not indicated in the examples and comparative examples, the operation or conditions of the conventional experimental steps described in the literature in this area can be carried out. Where the reagents or instruments used do not indicate the manufacturer, they are all conventional reagent products that can be obtained commercially. In all examples and comparative examples of the present application, the unit % represents the mass percentage content.

[0065] Example A

[0066] Step 1: Prepare the inner positive electrode

[0067] Conductive carbon black and carbon nanotubes in a mass ratio of 1:1 were added to PVDF glue and stirred evenly, and then lithium cobalt oxide (particle size Dv502 is 15μm) was added and stirred evenly to prepare a positive electrode active material slurry, which was coated on both sides of the positive electrode collector (i.e., 8μm thick aluminum foil), and the inner positive electrode sheet was obtained after baking and rolling. In the positive active layer of the inner positive electrode sheet, the mass fraction of lithium cobalt oxide is 97.6%, the mass fraction of PVDF is 1.05%, and the mass fraction of conductive carbon black and carbon nanotubes is 1.35%.

[0068] Step 2: Prepare the outermost positive electrode

[0069] The positive electrode active material slurry prepared in the first step is coated on one side of a 15μm thick aluminum foil, and then baked to obtain a single-sided positive electrode active layer. The gas-phase SiO2 particles (particle size Dv501 is 0.1μm) with a mass ratio of 95:5 are mixed with PVDF glue and stirred evenly to obtain a resistor layer slurry. The resistor layer slurry is coated on the surface of the single-sided positive electrode active layer away from the aluminum foil, and the outermost positive electrode sheet is obtained after baking and rolling.

[0070] Figure 2 This is a SEM image of the cross section of the outermost positive electrode sheet prepared in this embodiment. It can be seen from the image that the resistor layer is partially embedded in the positive electrode active layer. 2 The difference D between the maximum value of the thickness of the internal resistance layer and the minimum value of the thickness thereof is 1.617 μm.

[0071] Step 3: Prepare the negative electrode

[0072] 97.3% silicon carbon (silicon carbon contains 5% silicon), 0.5% conductive carbon black, 1.3% PVDF and 0.9% CMC are mixed evenly, and then an appropriate amount of deionized water is added to disperse them evenly to prepare a negative electrode active material slurry. The negative electrode active material slurry is coated on both sides of the carbon-coated copper foil, and the negative electrode sheet is obtained after baking and rolling.

[0073] Step 4: Preparation of lithium-ion secondary battery

[0074] The stacked cells are stacked and pressed in the order of outermost positive electrode sheet - separator - first negative electrode sheet - separator - first inner positive electrode sheet - separator ... separator - Nth negative electrode sheet - separator - outermost positive electrode sheet to obtain a stacked cell, and the cell is packaged, baked, injected, formed, sealed twice, sorted and OCV to obtain a lithium-ion secondary battery.

[0075] The separator includes a first adhesive layer, a substrate layer, a ceramic layer and a second adhesive layer which are stacked in sequence, the first adhesive layer is bonded to the negative electrode sheet, and the second adhesive layer is bonded to the positive electrode sheet. A commercially available conventional electrolyte is used, and the content of the carboxylic acid ester solvent in the electrolyte is 25%.

[0076] Example 1-1

[0077] Except for the following contents, the rest is the same as Example A.

[0078] The mass ratio of gas-phase SiO2 particles to PVDF glue in the resistor layer slurry is 90:10.

[0079] Example 1-2

[0080] Except for the following contents, the rest is the same as Example A.

[0081] The mass ratio of gas-phase SiO2 particles to PVDF glue in the resistor layer slurry is 85:15.

[0082] Examples 1-3

[0083] Except for the following contents, the rest is the same as Example A.

[0084] The mass ratio of gas-phase SiO2 particles to PVDF glue in the resistor layer slurry is 80:20.

[0085] Example 2-1

[0086] Except for the following contents, the rest is the same as Example A.

[0087] The particle size Dv501 of the gas-phase SiO2 particles is 0.01 μm.

[0088] Example 2-2

[0089] Except for the following contents, the rest is the same as Example A.

[0090] The particle size Dv501 of the gas-phase SiO2 particles is 0.2 μm, and the particle size Dv502 of the lithium cobalt oxide is 10 μm.

[0091] Example 2-3

[0092] Except for the following contents, the rest is the same as Example A.

[0093] The particle size Dv501 of the gas-phase SiO2 particles is 1 μm, and the particle size Dv502 of the lithium cobalt oxide is 20 μm.

[0094] Example 3-1

[0095] Except for the following contents, the rest is the same as Example A.

[0096] The thickness H1 of the resistor layer is 6 μm.

[0097] Example 3-2

[0098] Except for the following contents, the rest is the same as Example A.

[0099] The thickness H1 of the resistor layer is 0.5 μm.

[0100] Example 3-3

[0101] Except for the following contents, the rest is the same as Example A.

[0102] The thickness H2 of the positive electrode active layer is 55 μm.

[0103] Embodiment 3-4

[0104] Except for the following contents, the rest is the same as Example A.

[0105] The thickness H2 of the positive electrode active layer is 80 μm.

[0106] Example 4-1

[0107] Except for the following contents, the rest is the same as Example A.

[0108] The content of the carboxylic acid ester solvent in the electrolyte is 50%.

[0109] Example 4-2

[0110] Except for the following contents, the rest is the same as Example A.

[0111] The content of the carboxylic acid ester solvent in the electrolyte is 10%.

[0112] Example 4-3

[0113] Except for the following contents, the rest is the same as Example A.

[0114] The content of carboxylic acid ester solvent in the electrolyte is 30%, and the content of PVDF glue in the resistor layer slurry is 20%.

[0115] Example 4-4

[0116] Except for the following contents, the rest is the same as Example A.

[0117] The content of carboxylic acid ester solvent in the electrolyte is 10%, and the content of PVDF glue in the resistor layer slurry is 20%.

[0118] Example 5-1

[0119] Except for the following contents, the rest is the same as Example A.

[0120] The particle size Dv501 of the gas-phase SiO2 particles is 0.9 μm.

[0121] Example 5-2

[0122] Except for the following contents, the rest is the same as Example A.

[0123] The mass ratio of gas-phase SiO2 particles to PVDF glue in the resistor layer slurry is 96:4.

[0124] Example 5-3

[0125] Except for the following contents, the rest is the same as Example A.

[0126] The particle size Dv501 of the gas-phase SiO2 particles is 2 μm.

[0127] Example 5-4

[0128] Except for the following contents, the rest is the same as Example A.

[0129] The thickness H2 of the positive electrode active layer was 14.5 μm.

[0130] Example 5-5

[0131] Except for the following contents, the rest is the same as Example A.

[0132] The content of carboxylic acid ester solvent in the electrolyte is 40%, and the content of PVDF glue in the resistor layer slurry is 4.8%.

[0133] Example B

[0134] Step 1: Prepare the inner positive electrode

[0135] Conductive carbon black and carbon nanotubes in a mass ratio of 1:1 are added to PVDF glue and stirred evenly, and then lithium iron manganese phosphate (particle size Dv502 is 10μm) is added and stirred evenly to prepare a positive electrode active material slurry, which is coated on both sides of the positive electrode collector (i.e., 10μm thick aluminum foil), and the inner layer positive electrode sheet is obtained after baking and rolling. In the positive electrode active layer of the inner layer positive electrode sheet, the mass fraction of lithium iron manganese phosphate is 97%, the mass fraction of PVDF is 1%, and the mass fraction of conductive carbon black and carbon nanotubes is 2%.

[0136] Step 2: Prepare the outermost positive electrode

[0137] The positive electrode active material slurry prepared in the first step is coated on one side of a 20μm thick aluminum foil, and a single-sided positive electrode active layer is obtained after baking. Calcium oxide (particle size Dv501 is 0.1μm) with a mass ratio of 82:18 is mixed with PVDF glue and stirred evenly to obtain a resistor layer slurry. The resistor layer slurry is coated on the surface of the single-sided positive electrode active layer away from the aluminum foil, and the outermost positive electrode sheet is obtained after baking and rolling. Among them, the thickness H2 of the positive electrode active layer is 40μm, the thickness H1 of the resistor layer is 2μm, and the resistor layer is partially embedded in the positive electrode active layer. The unit area mm of the resistor layer 2 The difference D between the maximum value of the thickness of the internal resistance layer and the minimum value of the thickness thereof is 1.1 μm.

[0138] Step 3: Prepare the negative electrode

[0139] 97.3% silicon carbon (silicon carbon contains 10% silicon), 0.5% conductive carbon black, 1.3% PVDF and 0.9% CMC are mixed evenly, and then an appropriate amount of deionized water is added to disperse them evenly to prepare a negative electrode active material slurry. The negative electrode active material slurry is coated on both sides of the carbon-coated copper foil, and the negative electrode sheet is obtained after baking and rolling.

[0140] Step 4: Preparation of lithium-ion secondary battery

[0141] The stacked cells are stacked and pressed in the order of outermost positive electrode sheet - separator - first negative electrode sheet - separator - first inner positive electrode sheet - separator ... separator - Nth negative electrode sheet - separator - outermost positive electrode sheet to obtain a stacked cell, and the cell is packaged, baked, injected, formed, sealed twice, sorted and OCV to obtain a lithium-ion secondary battery.

[0142] The separator includes a first adhesive layer, a substrate layer, a ceramic layer and a second adhesive layer which are stacked in sequence, the first adhesive layer is bonded to the negative electrode sheet, and the second adhesive layer is bonded to the positive electrode sheet. A commercially available conventional electrolyte is used, and the content of the carboxylic acid ester solvent in the electrolyte is 15%.

[0143] Example C

[0144] Step 1: Prepare the inner positive electrode

[0145] After adding conductive carbon black to PVDF glue and stirring evenly, add nickel cobalt manganese oxide NCM811 (particle size Dv502 is 12μm) and stir evenly to prepare positive electrode active material slurry, which is coated on both sides of the positive electrode collector (i.e. 8μm thick aluminum foil), and then baked and rolled to obtain the inner positive electrode sheet. In the positive electrode active layer of the inner positive electrode sheet, the mass fraction of NCM811 is 98%, the mass fraction of PVDF is 1.1%, and the mass fraction of conductive carbon black is 0.9%.

[0146] Step 2: Prepare the outermost positive electrode

[0147] The positive electrode active material slurry prepared in the first step is coated on one side of an 18μm thick aluminum foil, and a single-sided positive electrode active layer is obtained after baking. Alumina (particle size Dv501 is 0.08μm) with a mass ratio of 88:12 is mixed with PVDF glue and stirred evenly to obtain a resistor layer slurry. The resistor layer slurry is coated on the surface of the single-sided positive electrode active layer away from the aluminum foil, and the outermost positive electrode sheet is obtained after baking and rolling. Among them, the thickness H2 of the positive electrode active layer is 60μm, the thickness H1 of the resistor layer is 4μm, and the resistor layer is partially embedded in the positive electrode active layer. The unit area mm of the resistor layer 2 The difference D between the maximum value of the thickness of the internal resistance layer and the minimum value of the thickness thereof is 1.8 μm.

[0148] Step 3: Prepare the negative electrode

[0149] 98% silicon carbon (silicon carbon contains 7% silicon), 0.5% conductive carbon black, 1% PVDF and 0.5% CMC are mixed evenly, and then an appropriate amount of deionized water is added to disperse them evenly to prepare a negative electrode active material slurry. The negative electrode active material slurry is coated on both sides of the carbon-coated copper foil, and the negative electrode sheet is obtained after baking and rolling.

[0150] Step 4: Preparation of lithium-ion secondary battery

[0151] The stacked cells are stacked and pressed in the order of outermost positive electrode sheet - separator - first negative electrode sheet - separator - first inner positive electrode sheet - separator ... separator - Nth negative electrode sheet - separator - outermost positive electrode sheet to obtain a stacked cell, and the cell is packaged, baked, injected, formed, sealed twice, sorted and OCV to obtain a lithium-ion secondary battery.

[0152] The separator includes a first adhesive layer, a substrate layer, a ceramic layer and a second adhesive layer which are stacked in sequence, the first adhesive layer is bonded to the negative electrode sheet, and the second adhesive layer is bonded to the positive electrode sheet. A commercially available conventional electrolyte is used, and the content of the carboxylic acid ester solvent in the electrolyte is 30%.

[0153] Example D

[0154] Step 1: Prepare the inner positive electrode

[0155] Conductive carbon black and carbon nanotubes in a mass ratio of 1:1 were added to PVDF glue and stirred evenly, and then lithium nickelate (particle size Dv502 was 18 μm) was added and stirred evenly to prepare a positive electrode active material slurry, which was coated on both sides of the positive electrode collector (i.e., 9 μm thick aluminum foil), and then baked and rolled to obtain an inner positive electrode sheet. In the positive electrode active layer of the inner positive electrode sheet, the mass fraction of lithium nickelate was 97.2%, the mass fraction of PVDF was 1.2%, and the mass fraction of conductive carbon black and carbon nanotubes was 1.6%.

[0156] Step 2: Prepare the outermost positive electrode

[0157] The positive electrode active material slurry prepared in the first step is coated on one side of the 25μm thick aluminum foil, and a single-sided positive electrode active layer is obtained after baking. Titanium oxide (particle size Dv501 is 0.01μm) with a mass ratio of 93:7 is mixed with PVDF glue and stirred evenly to obtain a resistor layer slurry. The resistor layer slurry is coated on the surface of the single-sided positive electrode active layer away from the aluminum foil, and the outermost positive electrode sheet is obtained after baking and rolling. Among them, the thickness H2 of the positive electrode active layer is 70μm, the thickness H1 of the resistor layer is 1μm, and the resistor layer is partially embedded in the positive electrode active layer. The unit area mm of the resistor layer 2 The difference D between the maximum value of the thickness of the internal resistance layer and the minimum value of the thickness thereof is 0.2 μm.

[0158] Step 3: Prepare the negative electrode

[0159] 97.3% silicon carbon (silicon carbon contains 8% silicon), 0.5% conductive carbon black, 1.3% PVDF and 0.9% CMC are mixed evenly, and then an appropriate amount of deionized water is added to disperse them evenly to prepare a negative electrode active material slurry. The negative electrode active material slurry is coated on both sides of the carbon-coated copper foil, and a negative electrode sheet is obtained after baking and rolling.

[0160] Step 4: Preparation of lithium-ion secondary battery

[0161] The stacked cells are stacked and pressed in the order of outermost positive electrode sheet - separator - first negative electrode sheet - separator - first inner positive electrode sheet - separator ... separator - Nth negative electrode sheet - separator - outermost positive electrode sheet to obtain a stacked cell, and the cell is packaged, baked, injected, formed, sealed twice, sorted and OCV to obtain a lithium-ion secondary battery.

[0162] The separator includes a first adhesive layer, a substrate layer, a ceramic layer and a second adhesive layer stacked in sequence, the first adhesive layer is bonded to the negative electrode sheet, and the second adhesive layer is bonded to the positive electrode sheet. A commercially available conventional electrolyte is used, and the content of the carboxylic acid ester solvent in the electrolyte is 36%.

[0163] Comparative Example 1

[0164] Except for the following contents, the rest is the same as Example A.

[0165] The outermost positive electrode sheet does not contain a resistor layer.

[0166] Comparative Example 2

[0167] Except for the following contents, the rest is the same as Example A.

[0168] Titanium dioxide is used instead of gas phase SiO2 to prepare the resistor layer slurry.

[0169] Comparative Example 3

[0170] Except for the following contents, the rest is the same as Example A.

[0171] Magnesium oxide is used instead of gas phase SiO2 to prepare the resistor layer slurry.

[0172] Test Case

[0173] 1. Particle size test

[0174] Choose ultrapure water as the dispersion medium, add 1g of the sample to be tested into 1L of the dispersion medium, and ultrasonicate for 60 minutes to fully disperse the sample to form a uniform suspension or dispersion. Pour the prepared sample suspension or dispersion into the sample pool, turn on the laser particle size analyzer for testing, and after the test is completed, the computer generates a particle size distribution diagram and related data report.

[0175] 2. Coating thickness test

[0176] Derived from the SEM image of the coating cross section.

[0177] 3. Adhesion test

[0178] Test equipment: tensile testing machine. Cut the rolled positive electrode into 25mm width, prepare a flat thin steel plate, and stick a double-sided tape on its center, stick the electrode on the double-sided tape, and make sure that the electrode and the tape are completely matched and fit to avoid test errors. Insert the steel plate with the fixed electrode into the lower clamp of the tensile testing machine and fix it vertically. Clamp the un-adhesive electrode on the upper clamp and fix it at 90° with the electrode of the lower clamp. Set the test width, peeling length and peeling speed parameters on the tensile testing machine. Start the test program, and the tensile testing machine will apply tensile force according to the set parameters and record the force value changes during the peeling process. After the test, data such as the peel strength curve and average value will be obtained.

[0179] 4. Surface resistance test

[0180] Discharge the battery to the lower limit voltage, then disassemble it in a drying room, take the positive electrode sheet and dry it naturally in the drying room, then place the positive electrode sheet on a surface resistance tester for testing.

[0181] 5. Resistivity test

[0182] Discharge the battery to the lower limit voltage, then disassemble it in a drying room, take the positive electrode sheet and dry it naturally in the drying room, then place the positive electrode sheet / negative electrode sheet on the resistivity tester for testing.

[0183] 6. Porosity test

[0184] Place the positive electrode in the true density tester, use helium as the medium, gradually pressurize the measuring chamber to a specified value, and then expand the helium into the expansion chamber. The equilibrium pressure of the two processes is automatically recorded by the instrument. According to the law of conservation of mass, the volume of the measuring chamber and the expansion chamber is calibrated by a standard ball, and the difference between the two is the true volume of the electrode. Then, the porosity is calculated according to the formula porosity = (electrode volume - true pole volume) / pole volume.

[0185] 7. Energy density retention test

[0186] The prepared finished battery was charged to full power at constant current and constant voltage at 25°C, and then discharged to 3.0V at 0.5C, and the discharged capacity was recorded as the battery capacity;

[0187] The prepared finished battery was charged to 50% SOC at 25°C, and the battery thickness was tested using 600g PPG;

[0188] Calculate volume energy density (ED) = battery capacity * platform voltage / battery length / width / thickness.

[0189] Calculate the ED loss rate = (energy density of comparative example 1 - energy density of embodiment) / energy density of comparative example 1.

[0190] 8. Cycle test

[0191] The prepared finished battery was subjected to 2C / 4C charge and discharge cycles at 25°C, and the battery capacity retention rate and expansion rate were confirmed after 800 cycles.

[0192] The battery was charged at 3C rate and discharged at 1C rate, and after 800 cycles, it was dissected to observe whether the outermost current collector was curled and whether the corresponding negative electrode sheet had lithium deposition. If the entire surface of the negative electrode sheet was golden yellow after dissection, it was determined that there was no lithium deposition; if there were 2-5 gray spots on the surface of the negative electrode sheet, it was determined to be slight lithium deposition; if there were more than 5 gray spots on the surface of the negative electrode sheet, it was determined to be lithium deposition.

[0193] The above test results are shown in Table 1-Table 2. In Table 1, “ / ” means no, R0 represents the resistivity of the single-sided positive electrode sheet, and D is the unit area mm 2 The difference between the maximum and minimum values ​​of the thickness of the resistor layer within the resistor layer, N1 is the adhesion between the resistor layer and the positive electrode active layer, N2 is the adhesion between the outermost current collector and the positive electrode active layer, N3 is the adhesion between the resistor layer and the thermal composite separator, R1 is the surface resistance of the single-sided positive electrode sheet, R2 is the surface resistance of the double-sided positive electrode sheet, R3 is the resistivity of the negative electrode sheet, P1 is the porosity of the single-sided positive electrode sheet, and P2 is the porosity of the double-sided positive electrode sheet.

[0194] Table 1

[0195]

[0196]

[0197] Table 2

[0198]

[0199]

[0200] Combining Table 1 and Table 2, it can be seen that the resistivity R0 of the single-sided positive electrode sheet in all embodiments is between 0.3-2 kΩ·cm, which can significantly improve the lithium plating problem of the negative electrode corresponding to the single-sided positive electrode sheet; while Comparative Example 1 does not have a resistance layer, and Comparative Example 2 uses titanium dioxide to prepare the resistance layer, which makes the resistivity of the single-sided positive electrode sheet lower, and Comparative Example 3 uses magnesium oxide to prepare the resistance layer, resulting in a higher resistivity of the single-sided positive electrode sheet. The above comparative examples cannot solve the problem of lithium plating at the negative electrode.

[0201] Compared with other embodiments, the unit area of ​​the resistance layer in embodiment 5-1 is 2 The difference between the maximum and minimum values ​​of the thickness of the internal resistance layer is less than 0.5 μm, which increases the thickness of the battery and causes a large loss in the battery energy density. In Example 5-4, the thickness of the positive active layer in the single-sided positive electrode sheet is too small, and the thickness of the resistance layer in Example 3-1 is too large, which causes a large loss in the battery energy density. The content of the adhesive in the resistance layer of Example 5-2 and Example 5-5 is too little, so that the impedance of the single-sided positive electrode sheet is small, and the local current density is large, resulting in slight lithium precipitation, which affects the battery cycle performance; and the particle size of the inorganic particles in the resistance layer of Example 5-3 is too large, resulting in poor bonding between the single-sided positive electrode sheet and the diaphragm, which also affects the battery cycle performance.

[0202] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.

Claims

1. A laminated battery core, comprising a plurality of positive electrode sheets and a plurality of negative electrode sheets alternately stacked, a separator is arranged between adjacent positive electrode sheets and negative electrode sheets, and the outermost electrode sheet of the laminated battery core is a single-sided positive electrode sheet; characterized in that: The single-sided positive electrode sheet includes an outermost current collector, a positive active layer and a resistance layer stacked toward the inner direction of the laminated battery core, the resistance layer at least covers the surface of the positive active layer away from the outermost current collector, and the resistance layer faces the diaphragm; the resistivity R0 of the single-sided positive electrode sheet is 0.3kΩ·cm-2kΩ·cm.

2. The laminated battery cell according to claim 1, characterized in that: The unit area of ​​the resistor layer mm 2 The difference D between the maximum value of the thickness of the resistor layer and the minimum value of the thickness of the resistor layer satisfies: D ≥ 0.5 μm; and / or, the adhesion force N1 between the resistor layer and the positive electrode active layer and the adhesion force N2 between the outermost current collector and the positive electrode active layer satisfy: N1>N2; And / or, the thickness H1 of the resistance layer and the thickness H2 of the positive electrode active layer satisfy: H2 / H1≥5.

3. The laminated battery cell according to claim 1 or 2, characterized in that: The resistance layer includes 80%-95% of inorganic particles and 5%-20% of adhesive.

4. The laminated battery cell according to claim 3, characterized in that: The median particle size Dv501 of the inorganic particles and the median particle size Dv502 of the active particles in the positive electrode active layer satisfy: Dv502 / Dv501≥10; And / or, the inorganic particles include at least one of silicon dioxide, aluminum oxide, calcium oxide, titanium oxide, boehmite, magnesium oxide, and magnesium hydroxide.

5. The laminated battery cell according to claim 4, wherein the Dv501 is 0.01 μm-1 μm, preferably 0.01 μm-0.1 μm; And / or, the Dv502 is 10 μm-20 μm; And / or, N1 is 1.5 gf / mm-9 gf / mm; And / or, N2 is 0.3gf / mm-1gf / mm; And / or, H1 is 0.5 μm-6 μm; And / or, the H2 is 30 μm-80 μm.

6. The laminated battery cell according to claim 1 or 2, characterized in that: The inner positive electrode sheet disposed between the two outermost electrode sheets in the laminated battery core comprises a double-sided positive electrode sheet; The surface resistance R1 of the single-sided positive electrode sheet and the surface resistance R2 of the double-sided positive electrode sheet satisfy: R1>1 / 2R2; And / or, the porosity P1 of the single-sided positive electrode sheet and the porosity P2 of the double-sided positive electrode sheet satisfy: P2>P1.

7. The laminated battery cell according to claim 6, characterized in that: The R1 is 0.3Ω / cm-2Ω / cm; And / or, R2 is 0.2Ω / cm-2Ω / cm; And / or, the P1 is 15%-30%; And / or, P2 is 20%-40%; And / or, the thickness of the outermost current collector is 12 μm-25 μm; And / or, the thickness of the current collector of the double-sided positive electrode sheet is 6 μm-10 μm.

8. The laminated battery cell according to claim 1 or 2, characterized in that: The diaphragm disposed toward the resistor layer is a thermal composite diaphragm, and the adhesive force N3 between the thermal composite diaphragm and the resistor layer is 0.1 gf / mm-2 gf / mm.

9. The laminated battery cell according to claim 1 or 2, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer disposed on the surface of the negative electrode current collector, wherein the negative electrode active layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon material; The resistivity R3 of the negative electrode sheet satisfies: 60Ω·cm≥R3≥2Ω·cm.

10. A lithium ion secondary battery, characterized in that: A laminated battery cell comprising any one of claims 1 to 9; Preferably, the lithium-ion secondary battery further comprises an electrolyte, wherein the content of the carboxylic acid ester solvent in the electrolyte is A% and 50≥A≥10, The content of the adhesive in the resistor layer is B% and 20≥B≥5, and A and B satisfy: 10≥A / B≥0.5.

Citation Information

Patent Citations

  • Energy storage system based on conductivity-controllable polymer current collector and preparation process thereof

    CN113036148A

  • Positive pole piece and preparation method thereof, secondary battery and electronic device

    CN116111045A

  • Electrode assembly and battery

    CN116845252A

  • Positive plate and lithium ion battery

    CN118040257A

  • Positive pole piece, electrode assembly, battery monomer, battery and electric equipment

    CN118843951A

Cited By

  • Secondary battery and electronic device

    WO2026184152A1